Back Cover: Reactions of Group 4 Metallocenes with Monosubstituted Acetonitriles: Keteniminate Formation versus CC Coupling (Chem. Eur. J. 8/2015). Issue 8 (16th February 2015) - Becker, Lisanne; Haehnel, Martin; Spannenberg, Anke; Arndt, Perdita; Rosenthal, Uwe
<x xml:space="preserve">Abstract</x> Runaround 1, 2, or 3 In the Full Paper on page 3242 ff., U. Rosenthal et al. describe the reactions of Group 4 metallocenes with monosubstituted nitriles. Depending on the Cp ligand, the metal, and the temperature, the products consisted of 1, 2, or 3 former nitrile moieties. This is illustrated by using a wall with three doors. The metallocenes – shown as red and yellow figures – have to decide between doors 1, 2, and 3. By passing the wall they catch one, two, or three nitrile moieties and form the products shown on the right side.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>